The Representation of the West and the Ideological Position of the Author in Belayettira Baralinda - Thapa, Dharma Bahadur (Saptagandaki Journal, 2021)
Written by Tana Sarma Belayettira Baralinda [Roaming through England] is a pioneering work of travel account in Nepali literature. It recounts the author’s observations of European society during the mid-sixties of the twentieth century. The purpose of this paper is to see whether the author accepts the hegemonic discourse of the west of its progress and civilization or resists and contests it. For the textual analysis, it uses Antonio Gramsci’s concept of Hegemony, Michel Foucault’s Discourse theory and Edward Said’s notion of Orientalism and the generic parameters of travel writing. As the original text is in Nepali, the writer has translated the cited parts into English and wherever is necessary, the Nepali is also used followed by its English equivalent. This review finds that it undoubtedly is a classic work of travelogue in Nepalese literature which presents a vivid picture of Europe of the mid-sixties of the twentieth century. It is more varied and surpasses its predecessors like Jungabahadurko Belayet Yatra and it is more analytical and multifaceted. It has saved itself from the fault of admiring the west without being objective and critical. Thematically, it covers three areas: admiration of the west as the place of progress, plenty and freedom, sporadic critiquing its inhumanity and the expression of authorial ethos in the description of the west. The paper concludes that, despite sporadic moments of critiquing, Sarma’s travel account approves western hegemonic discourse.